The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1002/sce.20387
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating family group inquiry at science museum exhibits

Abstract: ABSTRACT:We describe a study of programs to deepen families' scientiÞc inquiry practices in a science museum setting. The programs incorporated research-based learning principles from formal and informal educational environments. In a randomized experimental design, two versions of the programs, called inquiry games, were compared to two control conditions. Inquiry behaviors were videotaped and compared at pretest and posttest exhibits. Family members were also interviewed about their perceptions and use of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 31 publications
6
104
1
3
Order By: Relevance
“…the adoption of the interactive interpretation systems and multimedia), of how social interaction and collaboration can be encouraged, and how exhibits can be better designed to facilitate family mindful learning (Gutwill & Allen, 2010;Sung, Chang, Hou, & Chen, 2010;vom Lehn, Heath, & Hindmarsh, 2002). the adoption of the interactive interpretation systems and multimedia), of how social interaction and collaboration can be encouraged, and how exhibits can be better designed to facilitate family mindful learning (Gutwill & Allen, 2010;Sung, Chang, Hou, & Chen, 2010;vom Lehn, Heath, & Hindmarsh, 2002).…”
Section: Family Visitors In Museumsmentioning
confidence: 99%
“…the adoption of the interactive interpretation systems and multimedia), of how social interaction and collaboration can be encouraged, and how exhibits can be better designed to facilitate family mindful learning (Gutwill & Allen, 2010;Sung, Chang, Hou, & Chen, 2010;vom Lehn, Heath, & Hindmarsh, 2002). the adoption of the interactive interpretation systems and multimedia), of how social interaction and collaboration can be encouraged, and how exhibits can be better designed to facilitate family mindful learning (Gutwill & Allen, 2010;Sung, Chang, Hou, & Chen, 2010;vom Lehn, Heath, & Hindmarsh, 2002).…”
Section: Family Visitors In Museumsmentioning
confidence: 99%
“…As discussed by Gutwill and Allen (2010), the use of techniques such as 'juicy questions' might also be useful here -particularly where such questions are used to facilitate cross-cultural meaning-making. As suggested elsewhere, developing science learning opportunities within…”
Section: Discussion/ Conclusionmentioning
confidence: 99%
“…(Sue, Participant, Activity 5: Robotic Show/Presentation) Sue's comments stand out because her primary motivator for attending was not her own learning but that of the young people she took along. Prior work has suggested that an individual's motivation can be key to increased educational impacts from such an experience (Falk et al, 1998), however this work suggests it may also occur at a more discreet level, when an individual does not anticipate any such outcome or where attendance with others can motivate adults (Gutwill and Allen, 2009;Rennie and Williams, 2006). Even when participants were in attendance for primarily educational reasons, they often appreciated the attempt to include more interaction:…”
Section: Engaging Educationallymentioning
confidence: 99%